2020
DOI: 10.5398/tasj.2020.43.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Different Grass Availabilities of Tropical Pasture on Performances and Carcasses of Lambs

Abstract: This study aimed to identify the best green-leaf offerings of Urochloa brizantha cv. Marandu for pasture-finished lambs receiving protein-energy supplementation at the rate of 1.6% of their body weights (BW). The animals were assigned into four treatments, which consisted of varied green-leaf offerings, namely, 105, 90, 75, or 60 g of dry matter/kg of body weight (BW). Sixty-eight contemporary Texel × mixed-breed lambs with an average initial BW of 22.6 kg were used over two years of experiment. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The non-alteration of the physico-chemical characteristics of the meat was a consequence of the little variation in the chemical composition of the cultivars. The pH values of the meat were within the range considered ideal for the correct establishment and resolution of rigor mortis and were close to those reported in other studies with beef sheep (Fernandes et al, 2013;Heimbach et al, 2020). Changes in pH was generally associated with some type of pre-slaughter stress (Li et al, 2014), with little influence from the diet to which the animal is subjected (Fernandes et al, 2013;Santos et al, 2020;Heimbach et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…The non-alteration of the physico-chemical characteristics of the meat was a consequence of the little variation in the chemical composition of the cultivars. The pH values of the meat were within the range considered ideal for the correct establishment and resolution of rigor mortis and were close to those reported in other studies with beef sheep (Fernandes et al, 2013;Heimbach et al, 2020). Changes in pH was generally associated with some type of pre-slaughter stress (Li et al, 2014), with little influence from the diet to which the animal is subjected (Fernandes et al, 2013;Santos et al, 2020;Heimbach et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Brachiaria brizantha cv. Marandu), it is observed that it exhibits good primary production indexes, vitality, seed production capacity, ability to make small and large ruminants present the maximum production potential, due to the supply of forage in adequate proportion and good nutritional value (GERMANO et al, 2018;EUCLIDES et al, 2019;GURGEL et al, 2020;HEIMBACH et al, 2020).…”
Section: Introductionmentioning
confidence: 99%